Experimental Animal Models for Moyamoya Disease: A Species-Oriented Scoping Review - Cao, Lei; Dong, Yang; Sun, Kaiwen; Li, Dongpeng; Wang, Hao; Li, Hongwei; Yang, Bo (Frontiers in Surgery, 2022)
Moyamoya disease (MMD) is a rare cerebrovascular disease characterized by progressive stenosis of large intracranial arteries and a hazy network of basal collaterals called moyamoya vessels. The etiology and pathogenesis of MMD are still obscure. The biggest obstacles in the basic research of MMD are difficulty in obtaining specimens and the lack of an animal model. It is necessary to use appropriate and rationally designed animal models for the correct evaluation. Several animal models and methods have been developed to produce an effective MMD model, such as zebrafish, mice and rats, rabbits, primates, felines, canines, and peripheral blood cells, each with advantages and disadvantages. There are three mechanisms for developing animal models, including genetic, immunological/inflammatory, and ischemic animal models. This review aims to analyze the characteristics of currently available models, providing an overview of the animal models framework and the convenience of selecting model types for MMD research. It will be a great benefit to identify strategies for future model generations.